Developing diagnostic test assessment to measure creative thinking skills of Biology preservice teacher students - Eliaumra, Eliaumra; Samaela, Dewi Purwasih; Muhdin, Nining Kasim (REID (Research and Evaluation in Education), 2022)
The research aims to develop a diagnostic test assessment to measure the creative thinking skills of biology preservice teacher students. This research and development used Thiagarajan's 4D (Define, Design, Develop, and Dissemination) model. The diagnostic test assessment was developed in the form of an essay test with five numbers of scoring rubrics. This research was conducted at the Biology Education Study Program, University of Sintuwu Maroso. The results of the expert validation of the assessment instrument are high, and the reliability value is high. The results of the test found that all questions were valid and reliable. The student's creative thinking skills obtained an average value of fluency of 75.01% in the high category, flexibility thinking skills of 64.13% in the medium category, originality thinking skills of 69.56% in the medium category, elaboration skills of 75.01% in the high category and evaluation skills of 75.07% in the high category. All students' creative thinking skills are in the moderate category with a score of 71.74%, and the follow-up to the diagnostic results is that the lecturer can provide remedial on several learning indicators that have not been achieved.